Inferior Colliculus Microcircuits - Eric Daniel Young (Frontiers Research Topics, 2015)
The inferior colliculus (IC) is a unique structure in the auditory system, located between the primary auditory nuclei of the brainstem and the thalamus. The existence of the complex neural circuits in the auditory brainstem and midbrain, lacking in other sensory systems, has motivated an outpouring of research on the circuitry and physiological properties of the IC. IC neurons receive ascending inputs from over 20 separate sources in the brainstem as well as a dense collection of descending connections from the cortex. It is richly connected to both the left and right ears through these circuits and a major theme in research on the IC has been its role in binaural interactions. A second theme is the role of descending circuits in modulating responses to sound in the IC. A third theme is understanding the sound processing that occurs at the level of the IC, essentially how the representation of sound in the IC differs from that in the two auditory nerves. The representation of sound in the IC is an intermediate step in the development of the cortical representation as well as in the development of many perceptual features of sounds. These characteristics have been documented for a number of computations, including sound localization, masking properties, robustness of the representation, and responses to temporal and spectral properties of sounds. This Research Topic aims to discuss a wide range of aspects of the structure and function of the IC in a way that will facilitate future research.